Development and validation of the Portuguese version of the Eating Disorder Diagnostic Scale - Santos, Isabel Olímpia Figueiredo dos (2022)
This article presents the psychometric properties for the Portuguese population of a brief self-report scale for diagnosing anorexia nervosa (AN), bulimia nervosa (BN), and binge-eating disorder (BED): the Eating Disorder Diagnostic Scale (Stice et al., 2000). Method: To study the psychometric properties of EDDS, an exploratory factor analysis was done first, followed by a confirmatory factor analysis. Results: The results of the exploratory factor analysis revealed the existence of three components and the confirmatory factor analysis showed a structure with three latent variables (Body and Weight Concerns, Binge Eating Behaviour and Compensatory Behaviours), with a second order variable (Eating Disorder Symptoms) with a good adjustment fit. The internal consistency and the test–retest correlations revealed an adequate reliability and the inter-correlations of the EDDS subscales with other measures of the same and different constructs, supported the convergent and discriminant validity of this measure. Conclusions: Summing up, the EDDS seems to be a useful measure to assess eating disorders symptomatology in the Portuguese population.